Abogados y apoderados en pleitos de tierras, Chiapas, 1833-1872 - María del Rocío Ortiz Herrera (Caravelle)
The article examines the role of lawyers and legal representatives in land disputes in various indigenous towns of Chiapas throughout the nineteenth century. It analyses the strategies that these legal representatives employed in the land trials, as well as the legal arguments they brought in play, in order to show some of the difficulties faced by indigenous peasants and poor ladinos while defending their lands before the courts.